The center effect in liver transplantation in the Eurotransplant region: a retrospective database analysis. (5th March 2018) - Blok, Joris J.; de Boer, Jacob D.; Putter, Hein; Rogiers, Xavier; Guba, Markus O.; Strassburg, Christian P.; Samuel, Undine; van Hoek, Bart; Hamming, Jaap F.; Braat, Andries E.; ,
Summary: Apart from donor and recipient risk factors, the effect of center‐related factors has significant impact on graft survival after liver transplantation (LT). To investigate this effect in Eurotransplant, a retrospective database analysis was performed, including all LT's in adult recipients (≥18 years) in the Eurotransplant region from 1.1.2007 until 31.12.2013. Additionally, a survey was sent out to all transplant centers requesting information on surgeons' experience and exposure. In total, 10 265 LT's were included (median follow‐up 3.3 years), performed in 39 transplant centers. Funnel plots showed significant differences in graft survival between the transplant centers. After correction for donor and recipient risk, with the Eurotransplant donor risk index (ET‐DRI) and the simplified recipient risk index (sRRI) and random effects, these differences diminished. Mean historical volume (in the preceding 5 years) was a significant ( P < 0.001), nonlinear marker for graft survival in the multivariate analysis. This study demonstrates that funnel plots can be used for benchmarking purposes in LT. Case‐mix correction can be performed with the use of the ET‐DRI and sRRI. The center effect encompasses the entire complex process of preoperative workup, operation to follow‐up.